Advancing sustainable development through circular economy and skill development in EV lithium-ion battery recycling: a comprehensive review - Chigbu, Bianca Ifeoma (Frontiers in Sustainability, 2024)
The rapid worldwide transition to electric vehicles (EVs), propelled by progress in lithium-ion battery (LIB) technology, brings opportunities and problems in sustainable development and resource management. This study examines how incorporating circular economy ideas and enhancing skills in EV LIB recycling can be a strategic approach to meeting the 2030 Agenda for Sustainable Development. The article explores the relationship between environmental sustainability, economic growth, and social fairness by studying EV battery recycling, the workforce skills gap, and the economic ramifications of a circular approach. Based on the existing literature, the study highlights the importance of circular economy practices in improving resource efficiency, decreasing environmental pollution, and supporting various Sustainable Development Goals (SDGs), especially those concerning responsible consumption and production (SDG 12), climate action (SDG 13), and industry, innovation, and infrastructure (SDG 9). The study highlights the significance of Education for Sustainable Development (ESD) in preparing the workforce with the essential skills to adapt to a more sustainable and circular economy. It also highlights significant obstacles in present recycling methods, such as technological limitations, legislative discrepancies, and the necessity for worldwide collaboration and standardization. The paper suggests practical policy suggestions and future research paths to improve the sustainability of EV battery recycling. The initiatives involve establishing global recycling standards, promoting circular economy models through incentives, boosting technological innovation, and facilitating international collaboration and knowledge exchange.